Support for children born of rape in the Democratic Republic of the Congo: mother’s experiences and challenges - Euphrasie Kaningini Wamunzila; Frieda Vandeninden (Conflict and Health)
Abstract The repercussions of rape extend far beyond the act itself. Women who become pregnant as a result of rape are frequently forced to keep unwanted children, as abortion is generally perceived as unacceptable and illegal within the community. The aim of this study is to examine the socioeconomic challenges encountered by mother of children born of rape in the care of this children. The methodological approach of this study is based on a qualitative analysis. Semi structured interviews were conducted with 33 female survivors of sexual violence with children born of rape in the eastern DRC in the Kabare territory of the Katana groupement. The findings reveal that while all survivors experience trauma, those who give birth require distinct support. Mothers face numerous challenges in their caregiving roles, including financial hardship, fear of employment, low educational levels, loss of assets, lack of spousal support, and social stigmatization. Consequently, children born of rape encounter significant obstacles, especially for boys, in accessing basic services because of their mothers’ trauma, absence of paternal support, maternal ignorance, and societal stigma. Specific measures should be taken to improve the quality of life for both mothers and children affected by rape, fostering resilience and empowering them to overcome the numerous challenges they face.